Systematic description of putative animal fossils from the early Ediacaran Lantian Formation of South China. (29th April 2016) - Wan, Bin; Yuan, Xunlai; Chen, Zhe; Guan, Chengguo; Pang, Ke; Tang, Qing; Xiao, Shuhai
Abstract: The early Ediacaran Lantian Formation in South China contains some of the oldest known representatives of morphologically complex macroorganisms, including various macroalgae and putative animals. The macroalgal fossils have been described previously in several publications, but no taxonomic treatment has been published for the putative animal fossils. This hampers our ability to fully evaluate and communicate the significance of these potentially important Ediacaran macrofossils. To address this deficiency, here we provide a systematic description of these putative animal fossils from the Lantian Formation, including four new genera and five new species: Lantianella laevis gen. et sp. nov., L. annularis gen. et sp. nov., Piyuania cyathiformis gen. et sp. nov., Qianchuania fusiformis gen. et sp. nov. and Xiuningella rara gen. et sp. nov. Morphological comparisons of these fossils and potential modern analogues are provided and critically assessed.